ANALISIS INVESTASI PADA INDUSTRI PENGECORAN PROPELLER KAPAL (STUDI KASUS : CV. ANTERO JAYA SAKTI) - Kondo, Yan; Siahaya, Yusuf; Leonard, Johannes (Jurnal MEKANIKAL, 2012)
This study aims to determine the amount of investment of a particular industry on a ship propeller foundry industry CV. Antero Jaya Sakti and production costs and selling prices for each product made ​​propeller. The research was conducted by collecting data on production and equipment of CV. Antero Jaya Sakti, as well as making observations on the propeller shops of Makassar, needs to know the number and type of propeller is required. In addition, calculation and data analysis to determine the total investment and total production costs and payback period is desired. The results showed that the investment needed to run the ship propeller foundry industry in CV. Antero Jaya Sakti is 28,139.69 with a payback period of 3.2 years, cost of production required is 7.2 and selling price for a propeller that is produced is 9.77. The results could give the assumption that the investment in the propeller foundry industry can be considered feasible.